Water-Cut Estimation Uncertainty from Microwave Sensors - Suma, M. N.; Sheila-Vadde, Aparna C.; Melapudi, Vikram; Km, Manoj Kumar (Proceedings of IEEE Sensors ..., 2018)
Accurate measurement of oil, water and gas flow without separation has always been a challenge in the oil and gas industry as it involves estimation of five different parameters. One of the critical parameters to estimate is Water-Cut (WC), which is the ratio of water flow rate to the total liquid flow rate. In this paper we employ microwave sensing techniques to measure WC. To establish the accuracy of microwave sensors for WC estimation a static mixer based approach is established with a ground truth accuracy of . Based on this ground truth the Water-Cut estimation accuracy is found to be ±1.5%. This paper is comprehensive summary of the experimental procedure, approach to estimate the uncertainty in reference Water-Cut and the performance of microwave sensors in estimating Water-Cut.